2019
DOI: 10.1007/s00521-018-03987-9
|View full text |Cite
|
Sign up to set email alerts
|

Neural computing for a low-frictional coatings manufacturing of aircraft engines’ piston rings

Abstract: The ''boost-diffusion'' low-pressure nitriding used to low-frictional coatings manufacturing of aircraft engines' piston rings is a nonsteady-state process; therefore, designing and prediction of the process' kinetics by analytical solutions of Fick's equations or numerical methods of diffusion are difficult, due to the nonlinear relationship between the diffusion coefficient and the rate of diffusion as well as nonsteady-state boundary conditions. The best solution in this case, as the practice and theory ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…The coefficient of friction is used in the y axis as a response value, while the first predictor appears in the x axis, 0.017 units. Similarly, in the case of SAE 10W40, the equation of the prediction model for the coefficient of friction is (38) with 𝑅 = 0.90 and S = 0.015, which means 90% accuracy in prediction of the actual coefficient of friction for the contact with an average error of 0.015 for the estimation. Finally, in the case of AWS 100, the regression model is given by Equation ( 39) with 𝑅 = 0.85 and S = 0.021 or 85% accurate prediction for the friction coefficient in terms of sliding velocity and Young's modulus of the coating with an average deviation from the observations of 0.021.…”
Section: Machine Learning Results Based On the Coefficient Of Frictionmentioning
confidence: 99%
See 1 more Smart Citation
“…The coefficient of friction is used in the y axis as a response value, while the first predictor appears in the x axis, 0.017 units. Similarly, in the case of SAE 10W40, the equation of the prediction model for the coefficient of friction is (38) with 𝑅 = 0.90 and S = 0.015, which means 90% accuracy in prediction of the actual coefficient of friction for the contact with an average error of 0.015 for the estimation. Finally, in the case of AWS 100, the regression model is given by Equation ( 39) with 𝑅 = 0.85 and S = 0.021 or 85% accurate prediction for the friction coefficient in terms of sliding velocity and Young's modulus of the coating with an average deviation from the observations of 0.021.…”
Section: Machine Learning Results Based On the Coefficient Of Frictionmentioning
confidence: 99%
“…Senatore et al [37] found the lower average friction losses of piston ring-liner conjunction utilizing an Artificial Neural Network (ANN) model. Wołowiec-Korecka et al [38] trained a neural network model for the creation of low-frictional coatings on piston ring surfaces. They built an industrial tool to optimize the nitriding process under reduced pressure in the piston ring manufacturing process.…”
Section: Introductionmentioning
confidence: 99%
“…After the natural drying, the coated specimens have been annealed at 300 • C for 1 h in an inert N 2 atmosphere to sinter the cladded particles and to adhere them to the metallic substrate. Next, such preliminary prepared green compacts were thermo-chemically treated by FineLPN low-pressure nitriding [31] or alternatively, additionally treated by gas sulphonitriding in an active atmosphere containing ammonia gas and sulphur vapors [35]. Two options A and B of the multi-stage surface engineering process have been conducted and compared.…”
Section: Methodsmentioning
confidence: 99%
“…More intricate is the issue of cast iron nitriding, due to the presence of graphite precipitation in the microstructure [29,30] Recently, the new non-equilibrium, low-pressure nitriding process (FineLPN) has been developed. It may be used for creation of fully controlled phase structure of nitrided case both on steel and cast iron due to dedicated neural network computer support [31].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, more than one modeling program was required. The paper [19] described a neural network model and its training procedures based on data mining in the application, but only to monitor and control low-pressure nitriding process for the creation of low-frictional coatings. The authors [20] presented a numerical model based on the finite element method (FEM), which allows the deformations in the input elements to be determined, but with a step change in the material properties and constant cooling rate parameters.…”
Section: Introductionmentioning
confidence: 99%